2021
DOI: 10.1021/acs.cgd.1c01236
|View full text |Cite
|
Sign up to set email alerts
|

Central Metals to Guide the Bandgap of Hourglass-type Polyoxometalate Hybrids as Photocatalyst for the Reduction of Cr(VI)

Abstract: Visible-light photocatalytic reduction of hexavalent chromium Cr(VI) has become one of the most challenging topics in the field of environmental remediation. The key is to explore a stable and efficient photocatalyst. In this work, a series of highly reduced hourglass-type phosphomolybdate hybrids with molecular formula of (H 2 bpe) 3 {M-[P 4 Mo 6 O 31 H 8 ] 2 }•8H 2 O (M = Na for 1, Ca for 2, Cd for 3, Mn for 4, Zn for 5; bpe = trans-1,2-bi(4-pyridyl)-ethylene) were synthesized by hydrothermal methods and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…19,20 Apart from this, several hourglass-type POMbased catalysts have also been reported for photocatalytic Cr(VI) reduction. 4,21,22 The efficiency and recovery of POM-based photocatalysts for Cr(VI) reduction depend largely on (a) the prevention of the recombination of the photogenerated e − −h + pair and (b) the heterogeneous nature of the catalyst in water. In this study, we decided to use aryl sulfonium counterions (ASCs) to address the above two aspects simultaneously, i.e., to stabilize the photogenerated e − −h + pair on the cluster and to control the solubility of the hybrids in water.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 Apart from this, several hourglass-type POMbased catalysts have also been reported for photocatalytic Cr(VI) reduction. 4,21,22 The efficiency and recovery of POM-based photocatalysts for Cr(VI) reduction depend largely on (a) the prevention of the recombination of the photogenerated e − −h + pair and (b) the heterogeneous nature of the catalyst in water. In this study, we decided to use aryl sulfonium counterions (ASCs) to address the above two aspects simultaneously, i.e., to stabilize the photogenerated e − −h + pair on the cluster and to control the solubility of the hybrids in water.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Earlier reports on photocatalytic Cr(VI) reduction suggest that the electrons in the conduction band, generated after photoexcitation of the catalytic materials, are mainly responsible for photoreduction. 45,46 Therefore, in the present study, an experiment was conducted with AgNO 3 as an electron-trapping agent to shed more light on the mechanism of the photocatalytic reaction using hybrid 1 as a model catalyst. It was found that the presence of AgNO 3 in the reaction medium results in quenching the photocatalytic activity of hybrid 1.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…POMOCs combine the properties of POMs and MOCs, which can provide good cycling stability. 19,20 Therefore, syntheses and development of novel POMOCs is still fairly demanded and important.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the brilliant redox properties, strong electron transfer capability and tunable band gap structures, {P 4 Mo 6 }-based compounds have been applied in photocatalytic systems, such as CO 2 reduction, [28][29][30][31][32] dye degradation, 33,34 and Cr(VI) reduction. [35][36][37][38] In these reactions, the rapid and reversible multi-electron transfer characteristics of the {P 4 Mo 6 } units play an important role in improving the photocatalytic performance. Consequently, {P 4 Mo 6 }-based high-dimensional frameworks with highly insoluble structures and a broad spectral absorption range are expected to be excellent candidates for heterogeneous photocatalytic degradation of pollutants.…”
Section: Introductionmentioning
confidence: 99%